2013
DOI: 10.1021/jp403129g
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Integrated Carbon as a Light Absorber on the Coloration of Photonic Crystal-Based Pigments

Abstract: Three-dimensionally ordered macroporous (3DOM) materials prepared by colloidal crystal templating are examples of photonic crystals that can exhibit structural color. The color intensity can vary widely, from a pale, nearly white opalescence to vivid, brilliantly metallic colors. Such variations are observed even for 3DOM materials of a single nominal composition that exhibit virtually identical structural order in scanning electron micrographs and are prepared from the same colloidal crystal templates. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…[17] For colored 3DOM materials, it has been shown that a lightabsorbing substance within the structure greatly enhances the color intensity through the absorption of incoherently scattered light. [18] A similar enhancement of color intensities through the use of carbon nanoparticles infiltrated into opaline materials has also been observed. [19] For 3DOM materials, however, this absorber species can be created in situ during thermal processing and does not require additional integration steps.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…[17] For colored 3DOM materials, it has been shown that a lightabsorbing substance within the structure greatly enhances the color intensity through the absorption of incoherently scattered light. [18] A similar enhancement of color intensities through the use of carbon nanoparticles infiltrated into opaline materials has also been observed. [19] For 3DOM materials, however, this absorber species can be created in situ during thermal processing and does not require additional integration steps.…”
Section: Introductionmentioning
confidence: 56%
“…Building on recent advances that demonstrated the benefit of including carbon within the 3DOM oxide structure, [18] we employed pyrolysis in an inert gas atmosphere to maintain small levels of carbon that originated from decompo- Table 1. Structural and optical parameters for blue, green, and red 3DOM SiO 2 after grinding through a 38-μm sieve.…”
Section: Dom Sio 2 Structure and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering structural colors, originating from wavelength-selective scattering rather than absorption, has long been used in conjunction with molecular absorbers to produce visual effects in pigments (e.g. sparkle, color travel) [4][5][6][7][8][9][10][11][12][13][14]. Structural color is achieved by controlling the shape, layering, roughness or porosity of materials on length scales ranging from hundreds of nanometers up to millimeters [12,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…While the manufacturing of versatile structural color materials requires exquisite control of fabrication parameters on multiple length scales, it is decoupled from the specifics of the material chemistry or composition. Thus, in contrast to molecular dyes, a multitude of structural color effects can be generated from a single inert material [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%